Socioeconomic background of the learners' households and the issue of financial sustainability: the case of BRAC primary schools - Kalam, Md. Abul (BRAC Research and Evaluation Division (RED), 2019)
The study attempted to know the socio-economic condition of the community around school, their perception, views and opinions about BRAC primary schools and their quality; and people's willingness to pay for education. The study was conducted in two BRAC primary school areas of Rangpur and Modhupur having good and not so good performance respectively in paying fee. A census with about 400 households around each of the sample schools and group discussions with different groups were done for the purpose using structured questionnaire and checklists. The study reveals that household average education and annual income levels are found to play influential role in keeping the household regular or irregular in paying tuition fee as well as making them willing to pay for education. It is also observed that the proposed rate of tuition fee in BRAC primary schools is reasonable or even lower compared to private cost of primary education in Bangladesh and fee in other fee-paying schools in the locality. A significant proportion of the community around the schools is willing to pay the amount the BRAC primary schools proposed. However, BRAC primary schools could not attract much of the households those are socio-economically potential households for BRAC primary schools. Potential client for BRAe primary schools may be the households having average education of five or more years of schooling with (i) fair amount of land with service or business as main source of income and have more than one sources of income, or (ii) big land holding with agricultural work as main source of income and have more than one sources of income. Moreover, the study reveals a need for well-designed publicity about the schools and developing the schools in some aspects of those community people perceived as the characteristics of a good school.